Prematurity and ADHD in Childhood: An Observational Register-Based Study in Catalonia. Issue 7 (May 2021) - Perapoch, J.; Vidal, R.; Gómez-Lumbreras, A.; Hermosilla, E.; Riera, L.; Cortés, J.; Céspedes, M. C.; Ramos-Quiroga, J. A.; Morros, R.
Objective: To evaluate the association between prematurity (by the gestational week [gw]) and ADHD during childhood.Method: Observational, matched cohort study using data from children born in a tertiary-level hospital (Hospital Universitari Vall d'Hebron, Catalonia, Spain) during 1995-2007 and data from the Information System for the Development of Research in Primary Health Care (SIDIAP database, Catalonia, Spain).Results: Prevalence of ADHD increases as gestational age decreases, 12.7% for those born ≤28 gw, compared to 3.2% for those born after the 37 gw. The risk of developing ADHD in the non-premature children tends to increase as the gw decreases (35-36 gw, hazard ratio [HR] = 1.70, 95% confidence interval [CI] [1.19, 2.44]; 33-34 gw, HR = 3.38, 95% CI [2.08, 5.50]; 29-32 gw, HR = 2.37, 95% CI [1.54, 3.63]; and ≤28 gw, HR = 5.57, 95% CI [2.49, 12.46])Conclusion: Being born preterm is associated with a risk of developing ADHD, also in late preterm children (35-36 gw). Attention when taking care of these infants regarding their mental health must be made.